Cold stress elevates HSP70, TLR2 and TLR4 of indigenous chicken - RALTE, V; ALI, M AYUB; RAO, J M; TOLENKHOMBA, T C; MAYENGBAM, P (The Indian Journal of Animal Sciences, 2022)
The study revealed that cold stress elevates the expression of HSP70, TLR2 and TL4 of indigenous chicken. Increase in expression of HSP70 was most likely to have cryoprotective properties by elevating the TLR2 and TLR4 of indigenous chicken during cold stress.